PERJANJIAN SEWA-MENYEWA RUMAH KOS (INDEKOS) BAGI PARA PIHAK TERKAIT PERJANJIAN LISAN DI KOTA SINGARAJA - Dewa Ayu Putu Utari Praba; Ni Ketut Sari Adnyani; Ketut Sudiatmaka (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
This study aims to (1) find out the mechanism of boarding house rental agreement for the parties related to verbal agreements. (2) find out the implementation of a boarding house rental agreement for the parties related to verbal agreements in Singaraja City. (3) the legal consequences of the boarding house rental agreement for the parties related to the verbal agreements if one of the parties do a default. This research is a kind of empirical juridical research, with descriptive qualitative research, the research subjects are Owners and Tenants of Wijaya Kusuma Boarding House, Wahyu Murti, Baktiseraga, and Putri Lingga. Data collection, data presentation, and drawing conclusions. The results showed that; The mechanism of boarding house rental agreement for parties related to verbal agreements, namely inform the tenants to give the identity, payment of rent, information of the night- visit provisions, and agreement reached in the specified agreement in accordance with 1320 KUH Perdata; The implementation of the verbal agreement of boarding house rental in Singaraja City by means of the tenant have to come to the boarding house to meet the owner directly.